Whole-Transcriptome Analysis of Verocytotoxigenic Escherichia coli O157:H7 (Sakai) Suggests Plant-Species-Specific Metabolic Responses on Exposure to Spinach and Lettuce Extracts - Crozier, Louise; Hedley, Pete E.; Morris, Jenny; Wagstaff, Carol; Andrews, Simon C.; Toth, Ian; Jackson, Robert W.; Holden, Nicola J. (Frontiers in Microbiology, 2016)
Verocytotoxigenic Escherichia coli (VTEC) can contaminate crop plants, potentially using them as secondary hosts, which can lead to food-borne infection. Currently, little is known about the influence of the specific plant species on the success of bacterial colonisation. As such, we compared the ability of the VTEC strain, E. coli O157:H7 ‘Sakai’, to colonise the roots and leaves of four leafy vegetables: spinach (Spinacia oleracea), lettuce (Lactuca sativa), vining green pea (Pisum sativum) and prickly lettuce (L. serriola), a wild relative of domesticated lettuce. Also, to determine the drivers of the initial response on interaction with plant tissue, the whole transcriptome of E. coli O157:H7 Sakai was analysed following exposure to plant extracts of varying complexity (spinach leaf lysates or root exudates, and leaf cell wall polysaccharides from spinach or lettuce). Plant extracts were used to reduce heterogeneity inherent in plant-microbe interactions and remove the effect of plant immunity. This dual approach provided information on the initial adaptive response of E. coli O157:H7 Sakai to the plant environment together with the influence of the living plant during bacterial establishment and colonisation. Results showed that both the plant tissue type and the plant species strongly influence the short-term (1 hour) transcriptional response to extracts as well as longer-term (10 days) plant colonisation or persistence. We show that propagation temperature (37 versus 18 oC) has a major impact on the expression profile and therefore pre-adaptation of bacteria to a plant-relevant temperature is necessary to avoid misleading temperature-dependent wholescale gene-expression changes in response to plant material. For each of the plant extracts tested, the largest group of (annotated) differentially regulated genes were associated with metabolism. However, large-scale differences in the metabolic and biosynthetic pathways between treatment types indicate specificity in substrate utilisation. Induction of stress-response genes reflected the apparent physiological status of the bacterial genes in each extract, as a result of glutamate-dependent acid resistance, nutrient stress or translational stalling. A large proportion of differentially regulated genes are uncharacterised (annotated as hypothetical), which could indicate yet to be described functional roles associated with plant interaction for E. coli O157:H7 Sakai.